Recoding World Literature : Libraries, Print Culture, and Germany's Pact with Books - Mani, B. Venkat (Book collections on Project MUSE., 2016)
From the current vantage point of the transformation of books and libraries, B. Venkat Mani presents a historical account of world literature. By locating translation, publication, and circulation along routes of "bibliomigrancy"--the physical and virtual movement of books--Mani narrates how world literature is coded and recoded as literary works find new homes on faraway bookshelves.